Complete genome sequence of Thermus brockianus GE-1 reveals key enzymes of xylan/xylose metabolism - Schäfers, Christian; Blank, Saskia; Wiebusch, Sigrid; Elleuche, Skander; Antranikian, Garabed (BioMed Central, 2017)
Thermus brockianus strain GE-1 is a thermophilic, Gram-negative, rod-shaped and non-motile bacterium that was isolated from the Geysir geothermal area, Iceland. Like other thermophiles, Thermus species are often used as model organisms to understand the mechanism of action of extremozymes, especially focusing on their heat-activity and thermostability. Genome-specific features of T. brockianus GE-1 and their properties further help to explain processes of the adaption of extremophiles at elevated temperatures. Here we analyze the first whole genome sequence of T. brockianus strain GE-1. Insights of the genome sequence and the methodologies that were applied during de novo assembly and annotation are given in detail. The finished genome shows a phred quality value of QV50. The complete genome size is 2.38 Mb, comprising the chromosome (2,035,182 bp), the megaplasmid pTB1 (342,792 bp) and the smaller plasmid pTB2 (10,299 bp). Gene prediction revealed 2,511 genes in total, including 2,458 protein-encoding genes, 53 RNA and 66 pseudo genes. A unique genomic region on megaplasmid pTB1 was identified encoding key enzymes for xylan depolymerization and xylose metabolism. This is in agreement with the growth experiments in which xylan is utilized as sole source of carbon. Accordingly, we identified sequences encoding the xylanase Xyn10, an endoglucanase, the membrane ABC sugar transporter XylH, the xylose-binding protein XylF, the xylose isomerase XylA catalyzing the first step of xylose metabolism and the xylulokinase XylB, responsible for the second step of xylose metabolism. Our data indicate that an ancestor of T. brockianus obtained the ability to use xylose as alternative carbon source by horizontal gene transfer.